The Inevitability of Playing Politics as Chair:2018 - Domenick J Pinto (Academic Chairpersons Conference Proceedings, 2018)
Politics is a term often frowned upon as it pertains to the role of an academic leader. However as chair and now director of a school for 30 years it has become an essential yet sometimes unwanted aspect of the daily rigors of the position. This workshop explores the pros and cons of “playing politics” as a department chair and allows interactivity among participants in “what if” scenarios citing various literature references along the way
Keywords: leadership politics administration faculty staff